Application For Prediction Of The Spread Of The Covid-19 Outbreak In Manado - Vortuna, Vharadien Veronika; Jacobus, Agustinus; kambey, feisy diane (Jurnal Teknik Informatika, 2021)
Prediction system or system that predicts is a system that is used to predict something that will happen in the future or the future. Currently, the whole world, especially the city of Manado, is in a situation where the Covid-19 virus outbreak has paralyzed various aspects. Therefore, this study aims to provide information on predicting the spread of COVID-19 in Manado. Because this disease spreads to all corners of society easily, of course it requires information about the development of its spread in the future so that people can know the developments about the spread of the disease. The research entitled "Applications Â for Predicting the Spread of the Covid-19 Outbreak in Manado". This application can process covid-19 data that has been adjusted with the fb prophet method and use the Python programming language in order to get calculation results that can predict the spread of the covid-19 virus that will be infected in the future and will also display a prediction plot for the spread. This research will be displayed to the user in the form of a website application.Â Sistem prediksi atau sistem yang memperkirakan merupakan system yang di gunakan untukÂ  meramalkan sesuatu yang akan terjadi di masa mendatang atau masa yang akan datang. Saat ini seluruh Dunia terlebih khusus kota manado dalam situasi terserang wabah virus covid-19 yang melumpuhkan berbagai aspek. Oleh karena itu penelitian ini memiliki tujuan untuk memberikan informasi prediksi penyebaran covid-19 di Manado. Dikarenakan penyakit ini menyebar keseluruh penjuru masyarakat dengan mudah tentunya memerlukan informasi tentang perkembangan penyebarannya di masa yang akan datang agar supaya masyarakat dapat mengetahui perkembangan tentang penyebaran penyakit tersebut. Penelitian yang mengangkat judul â€œAplikasi Prediksi Penyebaran Wabah Covid-19 Di Manadoâ€. Aplikasi ini dapat mengolah data-data covid-19 yang telah di sesuaikan dengan metode fb prophet dan menggunakan bahasa pemrograman Python agar mendapatkan hasil perhitungan yang dapat memprediksi penyebaran virus covid-19Â  yang akan terjangkit dimasa yang mendatang dan juga akan menampilkan plot prediksi penyebaran. Penelitian ini akan di tampilkan kepada user dalam bentuk aplikasi website.